As concepções dos gestores do ensino fundamental sobre a educação ambiental escolar - Munhoz, Elzira Maria Bagatin (2013)
This research aimed to identify the concepts of the management of Elementary School about the practices of environmental education undertaken in school spaces. It involved four elementary schools in Joinville/SC that has developed environmental education activities. The research instrument was semi-structured interview, guided by a script of questions. Six managers answered the interview, among directors and pedagogical supervisors as promoters of environmental practices in their schools. The analysis were supported especially by Tardif, Tardif e Lessard; Canário; Ponte; Loureiro, Reigota and Carvalho. As being the protagonists of environmental education in schools were identified beyond managers, teachers from several areas when they develop activities outside the classroom, such as coordination of the library or computer room. The main factors that motivated the environmental practices in schools were an environmental competition sponsored by a corporation located in the city, the society and school expectation, besides personal and family motivation. Environmental education in school is perceived by managers as a collective and practical activity, which involves inside and outside community of the school, usually aimed at solving social environmental problems. The environmental actions undertaken tend to be prescriptive, based on a pragmatic and naturalistic concept of environmental education, and usually involve the routing of good environmental practices for the community around the school